2009
DOI: 10.1017/s1751731109004844
|View full text |Cite
|
Sign up to set email alerts
|

Return of testicular function after vaccination of boars against GnRH: consequences on testes histology

Abstract: Traditionally, male pigs are surgically castrated without anaesthesia to avoid later occurrence of the sex odour of androstenone in the carcass. Active immunization against gonadotropin-releasing hormone (GnRH) is a painless alternative which inhibits LH and thus steroidogenesis in the Leydig cells. In a preceding study we clarified the return of Leydig cell function after the last dose of antigen by measuring hormones, and found a considerable variation (10 to 24 weeks) till return of their function (testoste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
2

Year Published

2010
2010
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 40 publications
0
4
2
Order By: Relevance
“…Moreover, microscopic observation of testicular seminiferous tubules revealed that they had significantly atrophied, and there was almost no mature sperm in the lumens of the ISA 201 adjuvant group compared to the Gel 01 adjuvant and control groups. In the present study, no reversibility appeared uptil the late of this experiment, in contrast to many studies detected testosterone concentration with reversibility (Rottner and Claus, 2009). Based on the contradiction between the results of our study and Rottner's report (Rottner and Claus, 2009) it is thought that the reversibility of the T concentration may occur after a more extended term following immune castration.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Moreover, microscopic observation of testicular seminiferous tubules revealed that they had significantly atrophied, and there was almost no mature sperm in the lumens of the ISA 201 adjuvant group compared to the Gel 01 adjuvant and control groups. In the present study, no reversibility appeared uptil the late of this experiment, in contrast to many studies detected testosterone concentration with reversibility (Rottner and Claus, 2009). Based on the contradiction between the results of our study and Rottner's report (Rottner and Claus, 2009) it is thought that the reversibility of the T concentration may occur after a more extended term following immune castration.…”
Section: Discussioncontrasting
confidence: 99%
“…In the present study, no reversibility appeared uptil the late of this experiment, in contrast to many studies detected testosterone concentration with reversibility (Rottner and Claus, 2009). Based on the contradiction between the results of our study and Rottner's report (Rottner and Claus, 2009) it is thought that the reversibility of the T concentration may occur after a more extended term following immune castration. Previous studies reported that the serum LH and FSH levels rapidly increased after GnRH injection, and the LH level quickly reduced after injection of the GnRH antagonist.…”
Section: Discussioncontrasting
confidence: 99%
“…Zamaratskaia et al [26] reported inhibitory effects of vaccination against GnRH on male behavior and boar odor that can persist for 22 weeks after V2. In contrast, Claus et al [27] and Rottner and Claus [28] described individual differences in the resumption of testicular steroidogenesis from 10 to 24 weeks after V2. In the present study, fecal testosterone concentration began to increase at least ten weeks after V2.…”
Section: Discussionmentioning
confidence: 93%
“…For the GnRH antibody increase after V2, individual differences seem to play an important role [4,28,32,33]. Rottner and Claus [28] described maximum GnRH antibody peaks eight to eleven days after V2, whereas Claus et al [33] reported maxima already four to six days after V2. After this peak, GnRH antibody titers start to decrease continuously, explaining lower binding capacity in the early vaccinated groups in comparison to standard vaccinated groups [8].…”
Section: Discussionmentioning
confidence: 99%
“…The individual time span between the last immunization and slaughter in this study was 12 to 23 weeks for the EARLY group pigs and a resumption of steroidogenesis, which is accompanied by a rise of testosterone values, might be an explanation for higher testes weights [ 17 ]. Highly individual and variable time spans of 10 to 24 weeks from the last immunization to a resumption of testes function have been described earlier [ 24 , 25 ]. In these studies, the determined testosterone threshold in the serum for an assumed resumption of the testicular function was 0.5 ng/mL and therefore distinctly lower than values found for the EARLY group pigs in this study.…”
Section: Discussionmentioning
confidence: 99%